Digital subtraction angiography evaluation of extracranial and intracranial atherosclerotic arterial stenosis in patients of ischemic stroke with diabetes mellitus (Bangladesh Medical Journal, 2014)
Stroke is a medical emergency and can cause permanent neurological damage, even death. An ischemic stroke typically results from blockage of an artery that supplies the brain, most commonly a branch of one of the internal carotid arteries. In diabetic people, atheromatous lesions occur earlier in life and are more extensive and severe. This retrospective observational study was conducted among the patients having ischemic stroke with diabetes mellitus who were admitted in DMCH through out patient department during March 2010 to February 2011 to evaluate the extracranial and intracranial atherosclerotic arterial stenosis. A total of 30 patients with ischemic stroke and diabetes mellitus were included in the study. CT scan was done to every patient to confirm the diagnosis. Digital subtraction angiography was performed for complete evaluation. The mean age was 57.9 ±9.2 years with range from 43 to 80 years and male female ratio was 29:1. Among the 30 diabetic patients with ischemic stroke evaluated by DSA, 70% had extracranial stenosis where as 30 % had intracranial stenosis. Occurrence of extracranial atherosclerotic stenosis is more than intracranial atherosclerotic stenosis in ischemic stroke patients among diabetic population of Bangladesh. DOI: http://dx.doi.org/10.3329/bmj.v42i1.18977 Bangladesh Med J. 2013 Jan; 42 (1): 28-30